2016
DOI: 10.1039/c5ra20136e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity of ricinoleic acid glycosides

Abstract: The antibacterial properties of twenty-eight novel ricinoleic acid glycosides synthesized by Koenigs–Knorr glycosylation are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[2][3][4] Therefore, there are many derivatives of RA, also with interesting biological activities. [6][7][8] It has also been reported that RA exhibits some important properties, for instance, analgesic, pro-and anti-inflammatory, 9,10 as well as antinociceptive potential. [6][7][8] It has also been reported that RA exhibits some important properties, for instance, analgesic, pro-and anti-inflammatory, 9,10 as well as antinociceptive potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Therefore, there are many derivatives of RA, also with interesting biological activities. [6][7][8] It has also been reported that RA exhibits some important properties, for instance, analgesic, pro-and anti-inflammatory, 9,10 as well as antinociceptive potential. [6][7][8] It has also been reported that RA exhibits some important properties, for instance, analgesic, pro-and anti-inflammatory, 9,10 as well as antinociceptive potential.…”
Section: Introductionmentioning
confidence: 99%
“…The latest review of the literature 5 shows, for example, that such derivatives of (R)-RA as amides, esters or glycosides exhibit (in vitro) a potent antiproliferative effect on tumor cell lines and also antimicrobial activity. [6][7][8] It has also been reported that RA exhibits some important properties, for instance, analgesic, pro-and anti-inflammatory, 9,10 as well as antinociceptive potential. 11 It is crucial that to date only R-configured RA with the double bond in the cis configuration has been identified in nature and only this one is present in castor oil (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Ir3 caused more nucleic acid leakage than polymyxin B, a small lipopeptide membrane destabilizer. Similarly, complex Ir3 also resulted in the leakage of ortho-nitrophenyl-b-galactoside (ONPG), an intracellular enzyme which can produce O-nitrophenol with absorbance at 415 nm, 26,27 under the same condition (Fig. 4B).…”
Section: Antibacterial Mechanism Studies Of Ir3mentioning
confidence: 91%
“…Furthermore, the GC-MS analysis showed several bioactive compounds with important biological activity in ABP like Cinnamic acid, 4-hydroxy-3-methoxy (which has a promising potential as anticancer according to Mumtaz et al 2021), 9,10-Secocholesta-5,7,10(19)triene-3,24,25-triol, (3α,5Z,7E)-(which has anti-eczematic, anti-osteoporotic and inhibits prostaglandin-E2 9-reductase (Brintha et al, 2017), 1-Monolinoleoylglycerol trimethyl silyl ether (antimicrobial activity according to Al Bratty et al (2020), Sarreroside (which has respiratory analeptic effect, anti-cancer, antiprotozoa, dementia treatment, hepatoprotectant, and anti-eczematic according to Brintha et al (2017), Oxiraneoctanoic acid, 3-octyl-, cis-(Actually, Hussein et al (2016a) showed that Oxiraneoctanoic acid, 3-octyl-,methyl ester had antibacterial activity), 7,8-Epoxylanostan-11ol, 3-acetoxy-(which has antimicrobial, antiinflammatory effect according to Hassan et al (2014); Lee et al (2013), and n-Butyl ricinoleate (it was mentioned to the anti-bacterial and antimycobacterial properties of ricinoleic acidderived compounds (Kuppala et al, 2016).…”
Section: Gas Chromatography and Mass Spectrometry Analysis (Gc-ms) An...mentioning
confidence: 99%